2022
DOI: 10.3390/polym14051048
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Bi2O3 Nanoparticle Content on the γ-ray Interaction Parameters of Silicon Rubber

Abstract: In this study, synthetic silicone rubber (SR) and Bi2O3 micro- and nanoparticles were purchased. The percentages for both sizes of Bi2O3 were 10, 20 and 30 wt% as fillers. The morphological, mechanical and shielding properties were determined for all the prepared samples. The Linear Attenuation Coefficient (LAC) values of the silicon rubber (SR) without Bi2O3 and with 5, 10, 30 and 30% Bi2O3 (in micro and nano sizes) were experimentally measured using different radioactive point sources in the energy range var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The μ and μ m values of some commonly used shielding materials are shown in Fig. 3f [32][33][34][35][36][37][38][39] . As can be seen, the current MAPbI 3 /epoxy composites have superior gamma ray (59.5 keV) shielding ability, as indicated by their large μ and μ m values relative to most of the commonly used shielding materials.…”
Section: Gamma-ray Shielding Performance Of the Mapbi 3 / Epoxy Compo...mentioning
confidence: 99%
“…The μ and μ m values of some commonly used shielding materials are shown in Fig. 3f [32][33][34][35][36][37][38][39] . As can be seen, the current MAPbI 3 /epoxy composites have superior gamma ray (59.5 keV) shielding ability, as indicated by their large μ and μ m values relative to most of the commonly used shielding materials.…”
Section: Gamma-ray Shielding Performance Of the Mapbi 3 / Epoxy Compo...mentioning
confidence: 99%
“…The study demonstrated that nano dopant is more successful and effective in attenuating the photons. Abbas et al studied the effect of Bi 2 O 3 micro- and nano-particles content on silicon rubber’s (SR) γ-ray interaction parameters 35 . The attenuation coefficients of the obtained SR samples showed a clear advantage in lower energy levels compared to other energies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is an urgent need to find sustainable radiation shielding material to protect humans and the environment from the destructive impact of radiation [ 5 , 6 ]. Bismuth oxide Bi 2 O 3 was selected in this study due to its higher atomic number and nontoxicity; furthermore, it is considered a high-density material suitable for radiation shielding and has been applied to various materials such as glass [ 7 , 8 ], rubber [ 9 , 10 ], and building materials [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%